Orlicz Regularity for Non-Divergence Parabolic Systems with Partially Vmo Coefficients - Zhu, Maochun; Niu, Pengcheng; Feng, Xiaojing (MATHEMATICA SCANDINAVICA, 2015)
This work treats the interior Orlicz regularity for strong solutions of a class of non-divergence parabolic systems with coefficients just measurable in time and VMO in the spatial variables.